Framework of assessment for the evaluation of thinking skills of tertiary level students - Chan, Swee Heng; Ziguang, Yan (Australian International Academic Centre, 2015)
In the 21st century, students are required to master thinking skills in order to deal with many situations that arise in the tertiary environment which later would translate into the workplace. Nowadays, thinking skills play a vital role in tertiary education. To provide an approach for teachers, this paper identifies a 4-step model that can be implemented in test design with reference to Bloom’s Taxonomy for thinking skills. This model illustrates a feasible procedure of test construction built upon existing resource. The procedures can easily be applied to different fields of study. It provides an appropriate way for teachers who may want to add more ideas to their repertoire skills in addressing the learning of HOT (higher-order thinking) skills.